Synthesis, characterization and biocompatibility tests of magnetic nanoparticles - Azmoudeh, Aysa (Graduate School, 2023)
Nanotechnology advancements have surged recently in numerous fields, particularly in energy, environmental, electronic, and biological applications. Magnetic nanoparticles (MNPs) are one of the improvements that nanotechnology has brought to these application fields. MNPs are employed in biological, electrical, soil, or water filtration and catalytic applications. MNPs are one of them and are essential for the diagnosis and treatment of cancer. In research such as magnetic resonance imaging (MRI) for cancer diagnosis, like hyperthermia, magnetic nanoparticles are used as contrast agents. Particle sizes, shape, surface characteristics, biocompatibility, magnetic properties, and thermal and chemical stabilities are crucial for using nanomaterials in biomedical applications. Using magnetic nanoparticles will improve the surface area on which the medicine is carried and released because surface area increases as particle size decreases. Additionally, unless encased in protective layers, several iron oxide nanoparticles lose their chemical stability in bodily fluids. The efficiency of imaging applications could suffer from them becoming oxidized and having lower magnetization values. The concept of coating nanoparticles with protective layers has arisen to stop the degradation of magnetic nanoparticles in body fluids and to stop them from losing their magnetic capabilities. These types of materials are referred to as core/shell materials. Different inert materials are coated on the magnetic core to ensure its stability in biological settings. There have been studies on how to surround a metal with its noble metal or oxide to form a passivation layer. Silica and carbon-based (graphene, graphene oxide, etc.) shell materials are frequently chosen coating materials. MNPs and their encapsulations have been created using a variety of production techniques. Solvothermal synthesis could be used to create magnetic nanoparticles like Fe3O4. On the other hand, biocompatible surfaces can be created by encapsulating magnetic nanoparticles in various substances, including graphene. Although too many techniques were explored to encapsulate MNPs in graphene, chemical vapor deposition is one of the more effective ones. In this research, Fe3O4 and Fe3O4@rGO nanoparticles are synthesized by the solvothermal method, and for having high crystallinity and removal of organic compounds, the calcination process is applied by argon gases. Furthermore, encapsulation studies were carried out by feeding these substrates to the chemical vapor deposition (CVD) system and using methane (CH4) and hydrogen (H2) gases. The temperature (950°C), holding times (1 h), system pressures (50 mbar), and gas flow rates (100 mL/min) were investigated as variables. Leaching steps using HF and HCl acid solutions ensure the synthesis of pure powders free of uncoated Fe3O4 and demonstrate the chemical stability of synthesized nanoparticles. According to the magnetic saturation and coercivity values obtained from VSM tests, synthesized Fe3O4@rGO@graphene nanoparticles have soft ferromagnetic properties that demonstrate potential for biomedical and environmental applications. Magnetic saturation and coercivity values of Fe3O4@rGO@graphene were determined as approximately 139 emu/g and 402 Oe. Second, they are functionalized by coating Fe3O4@rGO@graphene core-shell nanoparticles with PMA-POEGMA polymer via Atom Transfer Radical Polymerization (ATRP). Cytotoxicity tests were carried out to demonstrate the usage of these nanoparticles in biomedicine. These nanoparticles were tested for biocompatibility (biocompatibility on MCF7 cancer cells for up to 48 h). In conclusion, Fe3O4 and Fe3O4@rGO nanoparticles were made via solvothermal synthesis. The calcination procedure is carried out using argon gases to achieve high crystallinity and the elimination of organic contaminants. These substrates were fed into the chemical vapor deposition (CVD) system together with methane (CH4) and hydrogen (H2) gases to conduct encapsulation tests. After leaching by HF and HCl acid solutions, Fe3O4@rGO@graphene nanoparticles are coated with PMA-POEGMA polymer. Then biocompatibilities were carried out to evaluate the materials' potential for biomedical applications (biocompatible up to 48 h on MCF7 cancer cells). The graphene encapsulation investigations are another thesis goal that optimization experiments on multilayer graphene-encapsulated magnetic nanoparticles (Fe3O4@rGO) in the CVD system. This work offers a novel contribution to the literature in terms of analyzing the biocompatibility of the encapsulated products made possible by optimizing the chemical vapor deposition technique. These magnetic nanomaterials, created in core/shell structures under optimal conditions and whose biocompatibility has been demonstrated by cytotoxicity testing, are candidates for biomedical applications.
Manyetik nanopartiküllerin sentezlenmesi, karakterizasyonu ve biyouyumluluk testlerinin gerçekleştirilmesi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: nanoparticles; nanoparçacıklar; biotechnology; biyoteknoloji; nanotechnology; nanoteknoloji